ADMINISTRATIVE LEGAL BASES OF OVERCOMING DISCRIMINATION BY THE SIGN OF SEXUAL ORIENTATION AND GENDER IDENTITY IN UKRAINE - Юринець, Юлія Леонідівна; Кудра, Ірина Андріївна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2018)
Purpose: find out the origins of non-traditional sexual orientation of individuals, the natural essence of the right to gender identity and the administrative and legal framework for the prevention of discrimination on these grounds. Methods: documentary analysis and synthesis, comparative analysis, objective truth, cognitive-analytical, etc. Results: it is proved that the right to free gender identity (the right to gender identity) is a natural human right that is to be protected along with other basic human rights. Discussion: ensuring the right to free gender identity (rights to gender identity) is the responsibility of every democratic society and part of Ukraine’s international obligations. The article is devoted to the study of the origins of non-traditional sexual orientation of individuals, the natural essence of the right to gender identity and the administrative and legal framework for the prevention of discrimination on these grounds. It is proved that the right to free gender identity (the right to gender identity) is a natural human right to be protected along with other fundamental human rights, and ensuring the right to gender identity (the right to gender identity) is the responsibility of every democratic society and Ukraine’s international obligations. The natural human right to free gender identity (the right to gender identity) is derived from the results of monitoring the behavior of animals, including mammals, which (behavior) indicates stable trends in homosexual behavior, as well as from the formation of possible bisexuality of individuals at the gene level. In this regard, gender identity and sexual orientation is not a free choice, but redefined by the natural features of the face. For example, when considering a court case «John Geddes Lawrence and Tyron Garner v. State of Texas» in the US Supreme Court, the latter took into account the fact that heterosexual and homosexual behavior are both normal aspects of human sexuality. Both have been documented in a wide variety of animal species. Since natural law is subject to protection by the state, it, the state, provides this protection by means of administrative law, which in a modern democratic society performs primarily law-enforcement and law-enforcement functions. The article deals with the indicated means, standardized on the basis of the Recommendation CM/Rec(2010)5 of the Committee of Ministers to member states on measures to combat discrimination on grounds of sexual orientation or gender identity (Adopted by the Committee of Ministers on 31 March 2010 at the 1081st meeting of the Ministers’ Deputies). The status of implementation of these Recommendations in Ukraine has been reviewed. Article 2-1 of the Labor Code was supplemented with a specific norm on the prohibition in labor relations of discrimination on grounds of gender identity, sexual orientation. The Order of the Ministry of Health of Ukraine dated 05.10.2016 № 1041 «On the establishment of medical and biological and socio-psychological indications for the change (correction) of sexual affiliation and approval of the form of primary accounting documentation and instructions for its completion» was adopted. At the same time, in the part of the LGBT component, the Action Plan for the implementation of the National Strategy for Human Rights for the period up to 2020, which was approved by the Cabinet of Ministers of Ukraine dated November 23, 2015 № 1393-р, is practically not implemented.